How Does Sustainable Management Practices Affect Weed Flora and Tuber Yield of Potato Crop in Mediterranean Environment? - Emanuele Radicetti; Khan Amanullah; Verdiana Petroselli; Mariam Atait; Mohamed Allam; Adil Mihoub; Aftab Jamal; Alireza Taab; Ghulam Haider; Morad Mirzaei; Roberto Mancinelli (Journal of Crop Health, 2024)
Intensive potato cultivation affects weed species composition by selecting dominant and competitive weeds that represent a constraint of potato productivity. Field experiments were conducted during 2015 and 2016 growing seasons to examine the effects of soil tillage (plowing (PL), spading (SM), sub soiling (SS)) and fertilizer source (mineral (Min) and organic (Org)) on potato yield and weed community under Mediterranean environment. A randomized complete block design with three replications was adopted. Weed density and biomass were measured at the potato harvesting time. Weed density was highest in SS, intermediate in SM, and lowest in PL (43.8, 40.3, and 28.8 plants m −2 ). Similar trend was observed in weed biomass. Weed density and biomass were higher in Org than Min (42.1 vs . 36.4 plants m −2 and 129.6 vs . 117.9 g m −2 , respectively). Perennial, monocot, and dicot weed species were the most abundant in subsoiling (13.1, 9.3 and 34.5 plants m −2 ). Density of perennial and dicot species were higher in Org than Min. Monocots were mostly linked with Min, while dicots were mainly associated with Org. Although tuber yield was higher in PL and Min (481.9 and 627.5 g m −2 of DM), it was affected by growing season and might be associated to SM and Org. Although the study shows that increased weed biodiversity in the system, achieved with more sustainable practices, proves to be an obstacle to potato production, the adoption of spading machine applied in combination with mineral and organic fertilizers could be a valid alternative to plowing. Further studies are required to develop sustainable agricultural techniques able to improve the competitive capacity of crops and reduce the selection of dominant weed species.